2018
DOI: 10.3390/nano8030167
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Coassembly Approach to All-In-One Multifunctional Nanoplatform for Synergistic Codelivery of Doxorubicin and Curcumin

Abstract: Synergistic combination therapy by integrating chemotherapeutics and chemosensitizers into nanoparticles has demonstrated great potential to reduce side effects, overcome multidrug resistance (MDR), and thus improve therapeutic efficacy. However, with regard to the nanocarriers for multidrug codelivery, it remains a strong challenge to maintain design simplicity, while incorporating the desirable multifunctionalities, such as coloaded high payloads, targeted delivery, hemodynamic stability, and also to ensure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…This smart-delivery system is particularly advantageous due to its noninvasive delivery and drug release, because the FA-DABA-SMA polymer circulates in the bloodstream and pH changes trigger drug release at the tumor site. 5 International Journal of Nanomedicine downloaded from https://www.dovepress.com/ by 44.224.250.200 on 18-Aug-2020 For personal use only. Preclinical evidence of curcumin-loaded FA-DABA-SMA polymer demonstrates significant toxicity and cell death in PANC1 pancreatic cancer cells, with the empty FA-DABA-SMA polymer being nontoxic.…”
Section: Novel Approaches To Smartnanoparticle Delivery Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…This smart-delivery system is particularly advantageous due to its noninvasive delivery and drug release, because the FA-DABA-SMA polymer circulates in the bloodstream and pH changes trigger drug release at the tumor site. 5 International Journal of Nanomedicine downloaded from https://www.dovepress.com/ by 44.224.250.200 on 18-Aug-2020 For personal use only. Preclinical evidence of curcumin-loaded FA-DABA-SMA polymer demonstrates significant toxicity and cell death in PANC1 pancreatic cancer cells, with the empty FA-DABA-SMA polymer being nontoxic.…”
Section: Novel Approaches To Smartnanoparticle Delivery Systemsmentioning
confidence: 99%
“…3 Currently, poor patient outcomes are attributed in part to the low stability, drug solubility and bioavailability, poor pharmacokinetic (PK) and pharmacodynamic (PD) parameters, aspecific distribution, cytotoxicity, and chemoresistance that are characteristic of traditional chemotherapeutic agents. 4,5 As a result, nanomedicine-based drug delivery has been of increasing research interest because NPs have been shown to substantially improve the therapeutic efficacy of chemotherapeutic agents by overcoming the various anatomical, physiological, chemical, and clinical barriers associated with intravenous drug administration. 4 However, the lack of efficacy in the clinic has made innovative NP-design and -delivery approaches increasingly important in the translation of these promising therapies from bench to bedside.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be because the surface charge of PELA x NPs‐pH7.4 was all below 15 mV and CUR loaded in hydrophobic core enhanced the compactness of the core hindering the protonation of PAEMA in the core. Moreover, as a measurement of fluorescence intensity of CUR, the value for images, as a gross approximation, was determined using the image analysis . As shown in Figure C, the gray values of CUR‐loaded PELA x NPs‐pH7.4 was obviously stronger than that of free CUR and there was no significant difference of the gray value among these five CUR‐loaded PELA x NPs‐pH7.4.…”
Section: Resultsmentioning
confidence: 99%
“…e synergistic antitumor effects of these nanoparticles have the following four aspects: (1) increased stability in blood circulation; (2) passive targeting due to EPR; (3) active targeting by recognition of CRGDK to neuropilin-1 receptor; and (4) high stability and low drug leakage under physiological pH, while the acidic environment dissociates the prodrugs to release DOX and CUR into the cells [83]. Based on the expression of Rf in the bloodbrain barrier and glioma cells, human TfR ligand T7 (sequence: HAIYPRH)-modified magnetic PLGA nanoparticle (MNP/T7PLGA NPs) target tumors and release PTX and CUR.…”
Section: Multifunctional Targeting Drug Delivery Systemsmentioning
confidence: 99%